APPLICATION OF REWARD AND PUNISHMENT IN THE FORMATION OF STUDENT MORALS AT MA'HAD DARUL IKHLASH PANYABUNGAN MANDAILING NATAL DISTRICT - Puli Taslim Nst; Khofifah Indah Alhusna Nasution; Al Hidayatun Nisa (Sean Institute, 2022)
Abstract This study aims to: Knowing the application of reward and punishment, knowing about the involvement of pesantren residents in the implementation of reward and punishment awards, knowing the kinds of rewards and punishments in Ma'had Darul Ikhlash, Panyabungan. This study uses a qualitative research type. Meanwhile, in obtaining the data, the author uses the method of observation, interviews, and documentation with ustadz/ustadzah informants, dormitory teachers, OPM and students. The results of this study are: 1) Application of reward and punishment if there are students who have good morals, carry out good activities. 2) There is involvement between fellow pesantren residents in the implementation of rewards and punishments in the Ma'had Darul Ikhlash environment starting from teachers, homerooms, caregivers dormitory to the principal. 3) Various kinds of rewards and punishments given to students can be in the form of repeating lessons until they can answer questions, give warnings or advise children, do cleanliness, stand in front of the class. Suggestions for this research are: 1) There is a written order and punishment for students who violate that is placed in school. 2) Not only students, it is better as a dormitory brother to participate so that the rules run even better. 3) Researchers hope that there will be directions for students before entering the class. 4) In the teaching and learning process, teachers should be more varied in providing material related to rewards and punishments. 5) The school is expected to make a program or policy related to reward and punishment. Keywords: Application, Reward and Punishment in Ma'had Darul Ikhlash